Two-ball problem revisited: Limitations of event-driven modeling - Müller, Patric; Pöschel, Thorsten (Physical Review E, 2011)
The main precondition of simulating systems of hard particles by means of event-driven modeling is the assumption of instantaneous collisions. The aim of this paper is to quantify the deviation of event-driven modeling from the solution of Newton's equation of motion using a paradigmatic example: If a tennis ball is held above a basketball with their centers vertically aligned, and the balls are released to collide with the floor, the tennis ball may rebound at a surprisingly high speed. We show in this article that the simple textbook explanation of this effect is an oversimplification, even for the limit of perfectly elastic particles. Instead, there may occur a rather complex scenario including multiple collisions which may lead to a very different final velocity as compared with the velocity resulting from the oversimplified model. © 2011 American Physical Society.